Does species‐level resolution matter? Taxonomic sufficiency in terrestrial arthropod biodiversity studies. Issue 4 (1st November 2012) - Timms, Laura L.; Bowden, Joseph J.; Summerville, Keith S.; Buddle, Chris M.; Didham, Raphael; Basset, Yves
Abstract Taxonomic sufficiency, or the suitability of substituting higher level taxonomic designations as response variables in community ecology analyses, is important in biodiversity studies from practical and fundamental perspectives. While there are many studies of taxonomic sufficiency in aquatic systems, there are few studies with terrestrial arthropods that examine the effects of taxonomic resolution on the interpretation of multivariate community data. We analysed data sets from three major arthropod orders (Araneae, Coleoptera, and Lepidoptera) using multivariate methods to determine whether altering the level of taxonomic resolution (species, genus, or family) affected patterns in community composition and beta diversity under various forest disturbance treatments. Overall patterns of community composition and beta diversity did not differ across taxonomic levels; however, patterns in group structure and significance of treatment effects were often stronger at species and/or genus level. The similarity between the outcomes of multivariate analyses at different levels of taxonomic resolution was related to within‐group taxonomic ratios; results were less consistent across levels of taxonomic resolution in groups with higher taxonomic ratios (i.e. more species per genus). We conclude that higher levels of taxonomic resolution will be sufficient for detecting the impacts of disturbance in lineages of terrestrial arthropods with higher levels of phylogenetic constraint, although this does not negate the necessity and importance of species‐level identifications in situations with sufficient resources and where study questions demand alpha taxonomy.